Modele edytorskie XIX-wiecznych polskich Biblii – próba identyfikacji - Zakonnik, Łukasz (The Biblical Annals, 2021)
The presented article reviews the publications of 19th century Polish Bibles in order to find editorial models according to which subsequent editions appeared. The work considers 62 editions that appeared in the years 1810–1900. 42 of them were based on the translation adopted in the Danzig Bible and 20 on the translation by Jakub Wujek. Among the analyzed editions, 23 were indicated, according to which subsequent Polish Bibles were published (in the 19th centuries). In addition to the identified editorial models, the work also proposes 7 basic editing lines.